RANCANG BANGUN APLIKASI HELP DESK BERBASIS WEB DI PT TRI STAR SURYA GEMILANG PURWOKERTO MENGGUNAKAN METODE DESIGN THINKING - Ni'am, Zuhrul Wafa; Muhamad Adito Pratama; M. Noviarsyah Dasaprawira (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2025)
This research aims to design and develop a web-based Help Desk application at PT Tristar Surya Gemilang Purwokerto using the Design Thinking method. The application is designed to enhance efficiency and transparency in managing complaints and expedite problem resolution through an integrated system. The research follows four main stages: Empathize, Define, Prototype, and Testing, focusing on user needs to create an effective solution. The results of the Blackbox Testing show that the application successfully meets the expected functionality for both admins and users, with features that align with user requirements. The developed system is expected to improve the IT team's performance in handling complaints and technical issues within the company.